PENGGUNAAN ALAR DAN BENZYLADENIN PADA MULTIPLIKASI MERISTEM PISANG - Astutik Astutik; Sutoyo Sutoyo; Astri Sumiati (Universitas Tribhuwana Tunggadewi, 2021)
Alar is a growth regulator that in certain concentrations can inhibit growth, shorten stem segments, strengthen stems to improve the quality of tissue-cultured seedlings. This study aimed to determine the effect of alar and Benzyl Adenin (BA) on banana meristem multiplication. The experiment was conducted in Tissue Culture Laboratory, Faculty of Agriculture, Tribhuwana Tunggadewi University, Malang. The study used a Completely Randomized Design consisting of two factors, namely alar concentration (A0 = 0 mg/l and A1 = 1 mg/l) and BA concentration (B1 = 1 mg/l, B2 = 3 mg/l, B3 = 5 mg/l and B4 = 7 mg/l). Observations were made for 12 weeks of culturing with the observation variables: shoot initiation, number of shoots/explants, number of leaves, and shoot height. The results showed that alar and BA did not significantly affect the development of banana meristems. The use of Alar caused the banana plantlets to be shorter and sturdy, while BA affected the number of shoots produced. BA 1 mg/l was able to increase more shoots.